In the footsteps of Raphael drawings from the Royal Library of Turin = Nel segno di Raffaello : disegni della Biblioteca Reale di Torino - Aceto, Angelamaria (Silvana editoriale, 2022)
The extraordinary legacy of the most talented draughtsman of all time, Raphael Sanzio, is explored in twenty-seven drawings from the collection of the Royal Library of Turin. From Perugino, Raphael's mentor, to Giulio Romano and Perino del Vaga, to Parmigianino and many others, the selection of works bear witness to the transformative and deep impact that Raphael's lesson exerted on the following generations of artists. Each drawing resonates with the master's ingenuity and skill, whether in the use of the chosen medium–earthy chalks, inks, and washes–or in the treatment of themes, affording the opportunity to get closer to his mind, while illustrating a fundamental chapter of Renaissance drawing culture
Impressum: Book published on the occasion of the exhibition "Nel segno di Raffaello", Turin, Royal Museums, Royal Library, 29 April - 17 July 2022
Keywords: Raffael -- 1483-1520; Rezeption; Umkreis; Schule; Ausstellungskatalog -- Biblioteca Reale -- 29.04.2022-17.07.2022 -- Turin; Bildband